1997
DOI: 10.1176/ajp.154.9.1265
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between birth complications and early maternal rejection in predisposing individuals to adult violence: specificity to serious, early-onset violence

Abstract: I t is being increasingly recognized that the interaction between environmental and biological factors may be particularly important in the development of crime and violence (1-3). Empirical support for such a view is nevertheless surprisingly limited. In a previous study conducted with Danish subjects (4), we found support for the biosocial perspective. That study tested the biosocial interaction hypothesis that birth complications, when combined with early maternal rejection of the infant, predispose to adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(26 citation statements)
references
References 24 publications
2
24
0
Order By: Relevance
“…However, studies have shown that children with birth complications are more likely to later develop antisocial and aggressive behavior (Raine, 2002), but birth complications may not by themselves predispose antisocial and aggressive behaviors, but will require the presence of an environmental risk factor (e.g., poor parenting, maternal rejection). In other words, the relationship between birth complications and antisocial and aggressive behavior is confounded by environmental risk factors (Hodgins et al ., 2001; Raine et al ., 1997). …”
Section: Heritability Of Aggression: Twin and Adoption Studiesmentioning
confidence: 99%
“…However, studies have shown that children with birth complications are more likely to later develop antisocial and aggressive behavior (Raine, 2002), but birth complications may not by themselves predispose antisocial and aggressive behaviors, but will require the presence of an environmental risk factor (e.g., poor parenting, maternal rejection). In other words, the relationship between birth complications and antisocial and aggressive behavior is confounded by environmental risk factors (Hodgins et al ., 2001; Raine et al ., 1997). …”
Section: Heritability Of Aggression: Twin and Adoption Studiesmentioning
confidence: 99%
“…Regarding the propensity to aggressive behavior, there are multiple factors interacting with each other. These factors include genetic [25] and environmental [6, 7] influences, as well as dysfunctional brain activity and/or anatomical brain damage, predominately localised to prefrontal and limbic structures [8, 9]. …”
Section: Introductionmentioning
confidence: 99%
“…It is well documented that early life environmental risk factors have detrimental effects on the long-term mental health of individuals and increasing evidence suggests that genotype can moderate the capacity of early environmental pathogens to alter risk for mental disorders [2]. In the development of adult antisocial and violent behavior, the environmental factors considered influential include in utero exposure to pathogens and birth complications [3], childhood abuse or neglect [4], [5], and family relationships, home environment, and other social variables [6].…”
Section: Introductionmentioning
confidence: 99%